The Bica São Tomé fossil site, Paraná Basin, Rio Grande do Sul, Brazil: A unique window to the dawn of the Mesozoic Era - Felipe Pinheiro; Atila A. Stock Da-Rosa (Journal of the Geological Survey of Brazil)
The Early Triassic is pivotal for understanding the recovery and diversification of post-extinction biotas, marking the initial emergence or early diversification of many modern life forms. This phase holds dual significance as it establishes the groundwork for contemporary biodiversity evolution and provides crucial insights into managing present ecological challenges. Focused efforts on the Sanga do Cabral Formation in the Paraná Basin unveil a critical opportunity for studying Early Triassic vertebrates in South America, offering a unique perspective on Western Gondwana's biotic recovery after the End-Permian Mass Extinction. Here, we review the geology and fossil record of the most important fossiliferous outcrop of the Sanga do Cabral Formation, the Bica São Tomé Fossil Site. Prospections at the outcrop have already recovered over two hundred specimens, including holotypes and representative materials of important Early Triassic taxa. Our review aims to demonstrate the relevance of the site and highlight strategies for its preservation. The site includes an unusual representation of archosauromorphs, although its content is dominated by procolophonids. Among the known localities of the Sanga do Cabral Formation, the Bica São Tomé Fossil Site stands out for the unique presence of well-preserved specimens in articulation, such as the nearly complete skeleton of the archosauromorph Teyujagua paradoxa. Even so, most of the record is dominated by fragmentary and reworked specimens. The Bica São Tomé site stands as a beacon for understanding Lower Triassic ecosystems in Latin America, presenting an unparalleled opportunity for Mesozoic exploration in Brazil. The Sanga do Cabral Formation, with its wealth of fossil evidence, promises to enrich our understanding of the Early Triassic period and its significance in shaping modern biodiversity.